Religious interactions in modern India - Fuchs, Martin,Ed; Vasudha Dalmia,Ed (OUP, 2019)
"Religions in South Asia have tended to be studied in blocks, whether in the various monolithic traditions in which they are now regarded, thus Hindu, Muslim, Buddhist, Sikh, Jain, and Christian, or indeed in temporal blocks : ancient, medieval, and modern. Analysing Hindu, Buddhist, Jain, Sikh, Islamic, and Christian traditions, this volume seeks to look at relationships both within and between religions focusing on the 19th and 20th centuries. The chapters explore not only the diversity and the multiplicity within each block, but also the specific forms of their coexistence with each other, whether in accord or in antagonism. The volume also views the interaction between 'reformed' and non-reformed branches within each of these purported monoliths. In going beyond existing debates on religious reform movements, the authors highlight the new forms acquired by religions and the ways in which they relate to each other, society and politics."--taken from back cover.